Association between psoriasis and lung cancer: two-sample Mendelian randomization analyses - Xiuqing Wang; Xiulan Wang; Hongkang Wang; Mingxing Yang; Wen Dong; Dan Shao (BMC Pulmonary Medicine, 2023)
Abstract Background Observational studies reported an association between psoriasis and risk of lung cancer. However, whether psoriasis is causally associated with lung cancer is unclear. Methods Genetic summary data of psoriasis were retrieved from two independent genome-wide association studies (GWAS). Genetic information of lung cancer was retrieved from GWAS of International Lung Cancer Consortium. A set of quality control steps were conducted to select instrumental tools. We performed two independent two-sample Mendelian randomization (MR) analyses and a meta-analysis based on the two independent MR estimates to assess the causal relationship between psoriasis and lung cancer (LUCA) as well as its subtypes, squamous cell carcinoma (LUSC) and adenocarcinoma (LUAD). Results Between-SNP heterogeneity was present for most MR analyses, whereas horizontal pleiotropy was not detected for all MR analyses. Multiplicative random-effect inverse variance weighted (IVW-MRE) method was therefore selected as the primary MR approach. Both IVW-MRE estimates from the two independent MR analyses suggested that there was no significant causal relationship between psoriasis and LUCA as well as its histological subtypes. Sensitivity analyses using other four MR methods gave similar results. Meta-analysis of the two IVW-MRE derived MR estimates yielded an odds ratio (OR) of 1.00 (95% CI 0.95–1.06) for LUCA, 1.01 (95% CI 0.93–1.08) for LUSC, and 0.97 (95% CI 0.90–1.06) for LUAD. Conclusion Our results do not support a genetic association between psoriasis and lung cancer and its subtypes. More population-based and experimental studies are warranted to further dissect the complex correlation between psoriasis and lung cancer.